Why School Olympiad Winners Are Excluded from Highly Selective Universities - Elena V. Gorbunova; Ekaterina V. Mayukova; Elena V. Ovakimyan; Danila M. Pavliuk (Вопросы образования)
This paper sheds light on opinions of reasons of dropout of students enrolled at university as Olympiad winners. This phenomenon is considered using the case of a highly selective university, which has faced a significant increase in the share of enrolled by Olympiads for state-funded places in the past few years. The study is carried out using a qualitative methodology, based on interviews with the organizers of the Olympiad movement and students of the Department of Mathematics and the Department of Computer Science. The individual and institutional reasons for the expulsion of students-winners of the Olympiads are singled out and the recommendations are proposed to reduce the dropout rate.